THE EFFECTIVENESS OF LEARNING VIDEOS ON INFORMATION PROCESSING IN MOSLEM STUDENTS - Muhammad Zulkifli Hariman; Raden Ayu Ria Ananda Sari; Rani Destari; Riska Trilia Utami (Taqrib : Journal of Islamic Studies and Education, 2023)
This study aims to determine the effectiveness of audio-visual learning on information processing abilities in moslem students. The existence of this research is because there are still many students who have difficulty understanding learning material. The hypothesis put forward is that there is an effect on the effectiveness of learning videos on the information processing abilities of moslem students. The research method used is One Group Pretest-Posttest Design. The subjects in this study were 30 moslem students. Data collection techniques using a questionnaire designed with a scale.